The future of scientific workflows. (January 2018) - Deelman, Ewa; Peterka, Tom; Altintas, Ilkay; Carothers, Christopher D; van Dam, Kerstin Kleese; Moreland, Kenneth; Parashar, Manish; Ramakrishnan, Lavanya; Taufer, Michela; Vetter, Jeffrey
Today's computational, experimental, and observational sciences rely on computations that involve many related tasks. The success of a scientific mission often hinges on the computer automation of these workflows. In April 2015, the US Department of Energy (DOE) invited a diverse group of domain and computer scientists from national laboratories supported by the Office of Science, the National Nuclear Security Administration, from industry, and from academia to review the workflow requirements of DOE's science and national security missions, to assess the current state of the art in science workflows, to understand the impact of emerging extreme-scale computing systems on those workflows, and to develop requirements for automated workflow management in future and existing environments. This article is a summary of the opinions of over 50 leading researchers attending this workshop. We highlight use cases, computing systems, workflow needs and conclude by summarizing the remaining challenges this community sees that inhibit large-scale scientific workflows from becoming a mainstream tool for extreme-scale science.